Exploring the Links Between Biophilic and Restorative Qualities of Exterior and Interior Spaces in Leon, Guanajuato, Mexico - Martínez-Soto, Joel; de la Fuente Suárez, Luis Alfonso; Ruiz-Correa, Salvador (Frontiers in Psychology, 2021)
The interactive role of the ecological, architectural, biophilic, and sensory qualities of outdoor and indoor spaces on the restorative experiences of urban inhabitants is little known. We analyze the restorative influence on mood states and situational stress related to exposure to vegetation proportion, spatial extension, landmark salience, biophilic architecture, people density, street visual access, olfactory pleasantness, and noise of 65 public spaces in a Mexican city. The environmental qualities of these places were analyzed with multidimensional scaling leading to eight space categories (e.g., historic squares with biophilic architecture, large parks, street scenes, and interiors with non-biophilic architecture). Ratings of the restorative potential, mood states, situational stress, olfactory pleasantness, and noise annoyance were evaluated on such places and modeled through a structural equation modeling. The model shows that the restorative influence of the environmental qualities on moods and stress was related to a decrease in experiences of negative moods and perceived stress, and an increase of positive mood states. Based on our findings, we discuss design guidelines emphasizing the relevance of including vegetation and built elements with biophilic qualities to create restorative environments.